Automatic Convergence in WIPL-D Software Using Python Scripting Algorithms - Ninkovic, Branislav; Music, Jasmin (2024 11th International Conference on Electrical, Electronic and Computing Engineering (IcETRAN), 2024)
Electromagnetic simulation software is indispensable in the daily work of RCS and antenna engineers. One of the crucial aspects that should be considered when using the results obtained by simulations is their accuracy. Accuracy is usually tested by automatic or manual convergence study. We observe WIPL-D software, a full 3D electromagnetic solver. This tool does not offer an automatic testing mechanism, thus we develop two such mechanisms using Python. WIPL-D released Python scripting library that we use to implement our algorithms. Two proposed algorithms are tested on a realistic scatterer project. Finally, we compared the efficiency of the two approaches.